2020
DOI: 10.3390/molecules25020301
|View full text |Cite
|
Sign up to set email alerts
|

Ammi Visnaga L., a Potential Medicinal Plant: A Review

Abstract: Ammi visnaga L. (Visnaga daucoides Gaertn., Family Apiaceae), also known as Khella Baldi or toothpick weed, is an annual or biennial herb indigenous to the Mediterranean region of North Africa, Asia, and Europe. The plant is known to have been used in traditional medicine a long time ago. Nowadays, it is used in modern medicine to treat many aliments such as renal colic and coronary insufficiency, and is used as an antioxidant, antifungal, and antibacterial, with a larvicidal effect on mosquito larvae. Peer-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 69 publications
1
62
0
1
Order By: Relevance
“…Both its umbels and fruits are known for their virtues on the urinary, cardiovascular systems, and oral health. It reduces hyperbilirubinemia and uremia 9 . According to Khan and Phyllis 10,11 studies, this plant extract prevents irritation, spasms in the urinary tract, and it has a diuretic action.…”
Section: Introductionmentioning
confidence: 99%
“…Both its umbels and fruits are known for their virtues on the urinary, cardiovascular systems, and oral health. It reduces hyperbilirubinemia and uremia 9 . According to Khan and Phyllis 10,11 studies, this plant extract prevents irritation, spasms in the urinary tract, and it has a diuretic action.…”
Section: Introductionmentioning
confidence: 99%
“…The first mechanism is mediated through the antioxidant's effect. 14 The second mechanism is through decreasing lipid levels such as cholesterol and triglycerides as reported in other studies. 15 Using rat model, we previously found that molecular defects in the brain white matter were beyond the events involved in the development of diabetes.…”
Section: Discussionmentioning
confidence: 83%
“…Ammi visnaga L. is an important medicinally active plant which is incorporated in several pharmaceutical preparations used worldwide [ 2 ]. The main pharmacologically active compounds in this plant are the furanochromones; khellin and visnagin.…”
Section: Discussionmentioning
confidence: 99%
“…Ammi visnaga L. (Apiaceae) is a popular commercial medicinal plant indigenous to Egypt and widely cultivated in the Mediterranean region and Europe [ 1 ]. The plant is industrially important as it is employed worldwide in many pharmaceutical products; either its extract or isolated active constituents [ 2 ]. It is widely used for its antispasmodic properties [ 3 ].…”
Section: Introductionmentioning
confidence: 99%